Double perspective in the colonial present - Svalastog, Anna Lydia; Wilson, Shawn; Gaski, Harald; Senior, Kate; Chenhall, Richard (Social Theory & Health, 2021)
This paper will explain the concept of double perspective and the impact that this cultural understanding may have on the health of the Indigenous peoples of Scandinavia. In inter-cultural communication, one set of meanings may be discernible to the outsider while a whole extra set of restricted or underlying meanings are only accessible for those people who have the cultural knowledge to discern them. These different sets of meanings embody a double perspective. It is not dual perspectives on the same reality but rather seeing two separate but overlapping realities. We will discuss the layers of meaning which are involved in the interactions between public healthcare institutions, clinicians and staff, and Indigenous people including the Sámi. These interactions are influenced by the impact of colonization and the ongoing epistemicide of Indigenous thought. By realising the improved resilience that a double perspective brings to Indigenous peoples, an awareness of the inclusion and exclusion of Indigenous persons, cultures and histories should become established in public institutions and in everyday life. A double perspective carries Sámi resilience, and should be understood as a key to support individual health, and also the collective wellbeing of a people living on their traditional yet colonized land.